The comparative meaning and structure of idiom in korean novel Phalshipinyeonsaeng Kim Ji Young (82 년생 김지영) with its Indonesian translation (study of semantics and syntax) - Herlina Riana (Journal of Korean Applied Linguistics, 2023)
Before expressing an opinion, people typically sort and choose their words, for example, selecting terms they believe to be more subtle. Hence, this research aims to discuss the comparison between the meaning and structure of idioms in a novel. The data were taken from the Korean novel as the source language, Phalshipinyeonsaeng Kim Ji Young (82 년생 김지영) by Cho Nam Joo and its translation in Indonesian as the target language, Kim Ji Yeong, Lahir Tahun 1982. Thus, the purpose of this research is to understand the comparison of meanings and structures in idioms of two different languages. This research used a descriptive qualitative method with the results of comparative meaning and structure of idioms from the source language and the target language by discussing semantic studies in the form of their lexical meanings and idiomatic meanings, as well as syntax studies through the constituent structures of these idioms as their theoretical approach. The findings showed the translation techniques, such as translating idioms into idioms, idioms into nonidioms, nonidioms into idioms, and translation by omission of entire idioms. Also, the findings showed the meaning equivalence whether it’s formal or dynamic equivalence in idioms translation that the translator used to convey the message from the author to the reader.